Chatbot Application for the Dissemination of Election Information - Sumitra, Irfan Dwiguna; Naufal, M; Pamungkas, D A; Widiarto, G (Universitas Komputer Indonesia, 2024)
The lack of media for election socialization that provides more accessibility for the deaf makes it difficult for them to obtain information given verbally, either by the KPU (The General Elections Commission) or the success team of candidate pairs who will compete. This condition could affect them to unvote. This research aims to design an application with an easy-to-use interface and help deaf people get accurate and accessible news and information. The method used to fulfill application development needs was a descriptive analysis method with a qualitative approach. This study used the Goal-Directed Design method to build an easy-to-use interface for deaf people. According to these applications, the deaf could easily understand election news information because videos are equipped with sign language and subtitles. These applications help the deaf quickly access and obtain the information about the election socialization that will hold and determine whom the candidates will compete in the election such as news feature, ask KPU, listen to reading, etc. The chatbot technology is expected to make the information search process more personal so that deaf people feel more comfortable using the application